Synthesis, Characterization, and Biological Studies of a Piperidinyl Appended Dipicolylamine Ligand and Its Rhenium Tricarbonyl Complex as Potential Therapeutic Agents for Human Breast Cancer - Subasinghe, Amali; Perera, Inoka C.; Pakhomova, Svetlana; Perera, Theshini (My University, 2016)
A novel ligand bearing a central piperidinyl sulfonamide group, N(SO2pip)dpa, and its corresponding Re tricarbonyl complex, [Re(CO)3(N(SO2pip)dpa)]+, have been synthesized in good yield. The methylene CH2 signal seen as a singlet (4.54 ppm) in a 1H NMRspectrumof the ligand inDMSO-𝑑6 appears as two doublets (5.39, 5.01 ppm) in a spectrumof the [Re(CO)3(N(SO2pip)dpa)]+ complex and confirms the presence ofmagnetically nonequivalent protons upon coordination to Re. Structural results revealed that theRe–N bond lengths fall within the normal range establishing coordination of ligand tometal.The presence of intraligand𝜋 → 𝜋∗ and𝑛 → 𝜋∗ transitions is indicated by the absorption peaks around 200–250 nm in UV-visible spectra. Absorption peaks in UVvisible spectra around 300 nmfor metal complexes were identified asMLCT transitions.The S–N stretch observed as a strong peak at 923 cm−1 forN(SO2pip)dpa appeared at a shorter frequency, at 830 cm−1 in an FTIR spectrum of the [Re(CO)3(N(SO2pip)dpa)]+. The intense fluorescence displayed by the N(SO2pip)dpa ligand has quenched upon coordination to Re. Relatively low IC50 values given by human breast cancer cells, MCF-7, (N(SO2pip)dpa = 139 𝜇M, [Re(CO)3(N(SO2pip)dpa)]+ = 360𝜇M) indicate that N(SO2pip)dpa and [Re(CO)3(N(SO2pip)dpa)]+ are promising novel compounds that can be further investigated on their usage as potential anticancer agents.